CREATING LEARNING MEDIA IN TEACHING ENGLISH AT SMP MUHAMMADIYAH 2 PAGELARAN ACADEMIC YEAR 2020/2021 - Anna Mardiana; Novita Eka Tristiana; Miftahul Jannah (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2021)
The pandemic Covid-19 currently demands teachers to be able to use technology in teaching and learning process. But in reality there are still many teachers who have not been able to utilize technology as using learning media. Therefore, the purpose of this research to produce interactive learning media based on Android using Ispring suit 9 and APK 2 Builder during pandemic Covid-19 at seven grade of SMP Muhammadiyah 2 Pagelaran in Academic year 2020/2021. The type of the research is a Research & Development, using ADDIE model. The result of this research and development is an Android learning media application that can help facilitate the delivery of materials with additional competency features, learning descriptive text, learning videos, and quizzes. that can be accessed offlline as well as the ease of installation in Android. This Learning Media has been validated by material experts and media experts whose results are very worthy to use in learing English in pandemic covid-19. So that the conclusion of interactive learning media based on Android using Ispring and APK 2 Builder can be used as learning resources and media support distance learning in pandemic Covid-19. They are more active in learning English descriptive text and understanding material in a fun way, especially in online learning. The pandemic Covid-19 currently demands teachers to be able to use technology in teaching and learning process. But in reality there are still many teachers who have not been able to utilize technology as using learning media. Therefore, the purpose of this research to produce interactive learning media based on Android using Ispring suit 9 and APK 2 Builder during pandemic Covid-19 at seven grade of SMP Muhammadiyah 2 Pagelaran in Academic year 2020/2021. The type of the research is a Research & Development, using ADDIE model. The result of this research and development is an Android learning media application that can help facilitate the delivery of materials with additional competency features, learning descriptive text, learning videos, and quizzes. that can be accessed offlline as well as the ease of installation in Android. This Learning Media has been validated by material experts and media experts whose results are very worthy to use in learing English in pandemic covid-19. So that the conclusion of interactive learning media based on Android using Ispring and APK 2 Builder can be used as learning resources and media support distance learning in pandemic Covid-19. They are more active in learning English descriptive text and understanding material in a fun way, especially in online learning. The pandemic Covid-19 currently demands teachers to be able to use technology in teaching and learning process. But in reality there are still many teachers who have not been able to utilize technology as using learning media. Therefore, the purpose of this research to produce interactive learning media based on Android using Ispring suit 9 and APK 2 Builder during pandemic Covid-19 at seven grade of SMP Muhammadiyah 2 Pagelaran in Academic year 2020/2021. The type of the research is a Research & Development, using ADDIE model. The result of this research and development is an Android learning media application that can help facilitate the delivery of materials with additional competency features, learning descriptive text, learning videos, and quizzes. that can be accessed offlline as well as the ease of installation in Android. This Learning Media has been validated by material experts and media experts whose results are very worthy to use in learing English in pandemic covid-19. So that the conclusion of interactive learning media based on Android using Ispring and APK 2 Builder can be used as learning resources and media support distance learning in pandemic Covid-19. They are more active in learning English descriptive text and understanding material in a fun way, especially in online learning. The pandemic Covid-19 currently demands teachers to be able to use technology in teaching and learning process. But in reality there are still many teachers who have not been able to utilize technology as using learning media. Therefore, the purpose of this research to produce interactive learning media based on Android using Ispring suit 9 and APK 2 Builder during pandemic Covid-19 at seven grade of SMP Muhammadiyah 2 Pagelaran in Academic year 2020/2021. The type of the research is a Research & Development, using ADDIE model. The result of this research and development is an Android learning media application that can help facilitate the delivery of materials with additional competency features, learning descriptive text, learning videos, and quizzes. that can be accessed offlline as well as the ease of installation in Android. This Learning Media has been validated by material experts and media experts whose results are very worthy to use in learing English in pandemic covid-19. So that the conclusion of interactive learning media based on Android using Ispring and APK 2 Builder can be used as learning resources and media support distance learning in pandemic Covid-19. They are more active in learning English descriptive text and understanding material in a fun way, especially in online learning. The pandemic Covid-19 currently demands teachers to be able to use technology in teaching and learning process. But in reality there are still many teachers who have not been able to utilize technology as using learning media. Therefore, the purpose of this research to produce interactive learning media based on Android using Ispring suit 9 and APK 2 Builder during pandemic Covid-19 at seven grade of SMP Muhammadiyah 2 Pagelaran in Academic year 2020/2021. The type of the research is a Research & Development, using ADDIE model. The result of this research and development is an Android learning media application that can help facilitate the delivery of materials with additional competency features, learning descriptive text, learning videos, and quizzes. that can be accessed offlline as well as the ease of installation in Android. This Learning Media has been validated by material experts and media experts whose results are very worthy to use in learing English in pandemic covid-19. So that the conclusion of interactive learning media based on Android using Ispring and APK 2 Builder can be used as learning resources and media support distance learning in pandemic Covid-19. They are more active in learning English descriptive text and understanding material in a fun way, especially in online learning. The pandemic Covid-19 currently demands teachers to be able to use technology in teaching and learning process. But in reality there are still many teachers who have not been able to utilize technology as using learning media. Therefore, the purpose of this research to produce interactive learning media based on Android using Ispring suit 9 and APK 2 Builder during pandemic Covid-19 at seven grade of SMP Muhammadiyah 2 Pagelaran in Academic year 2020/2021. The type of the research is a Research & Development, using ADDIE model. The result of this research and development is an Android learning media application that can help facilitate the delivery of materials with additional competency features, learning descriptive text, learning videos, and quizzes. that can be accessed offlline as well as the ease of installation in Android. This Learning Media has been validated by material experts and media experts whose results are very worthy to use in learing English in pandemic covid-19. So that the conclusion of interactive learning media based on Android using Ispring and APK 2 Builder can be used as learning resources and media support distance learning in pandemic Covid-19. They are more active in learning English descriptive text and understanding material in a fun way, especially in online learning.